Weak convergence theorem of generalized self-adaptive algorithms for solving split common fixed point problems - Raweerote Suparatulatorn (2020)
© 2020, Politechnica University of Bucharest. All rights reserved. In the present paper, we introduce a self-adaptive algorithm for solving the split common fixed point problem of demicontractive operators in real Hilbert spaces. Weak convergence result is discussed under suitable assumptions. Some numerical experiments are also given to support our main theorem. Moreover, applications are given to the split common null point problem and the split feasibility problem.